Pemanfaatan Minyak Sereh Wangi sebagai Zat Aditif untuk Meningkatkan Karakteristik Biodiesel B30 - Nisrina, Dian; Harunsyah, Harunsyah; Zaini, Halim (Politeknik Negeri Lhokseumawe, 2024)
The use of petroleum as fuel is currently very limited and cannot be renewed on a relevant human scale. The increasing demand for petroleum, including diesel, has resulted in increased dependence on resources. The use of diesel as fuel has a negative impact on the environment. To reduce the negative impacts caused, other fuel derivative products can be developed, namely biodiesel. One alternative to increase fuel efficiency and reduce pollution is to reformulate fuel with additives, namely citronella oil, which functions to enrich the oxygen content in the fuel. The purpose of this study was to determine the effect of variations in the addition of citronella oil volume and temperature on the characteristics of B30 biodiesel. This study was conducted using an experimental design method by varying the volume of citronella oil 0; 2; 4; 6; 8; 10 mL and temperatures of 30°C, 35°C, 40°C, 45°C, 50°C. The results showed that the addition of citronella oil with temperature variations was able to improve the characteristics of B30 biodiesel. The best variation is the addition of 4 mL of citronella oil at a temperature of 40 °C resulting in the highest viscosity value of 4.318 cSt, density of 836.41 kg/m3, cetane number of 67.9 and flash point value of 79°C. In this study, the data produced is in accordance with SNI in terms of viscosity, density, cetane number, and flash point.